Off-pump versus on-pump coronary artery bypass grafting in patient of impaired renal function (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
The purpose of this study was to compare the renal function in patients undergoing coronary artery bypass grafting in off-pump and on-pump having pre-operative impaired renal function. In the on-pump, the serum creatinine and urea levels were significantly increased on post-operative day 1, 3 and 7. On day 1, it was maximum, then gradually decreased but not reached to pre-operative level. In case of off-pump, serum creatinine and urea levels were significantly increased on post-operative day 1 and 3. On day 1, it was maximum. Then decreased and the serum creatinine reached below pre-operative level on day 7. In case of on-pump, the creatinine clearance rate was significantly decreased on post-operative day 1, 3 and 7. On day 1, it was minimum. Then gradually increased but not reached the pre-operative level. In case off-pump, the creatinine clearance rate was significantly decreased on day 1 and 3. On day 1, it was minimum, then gradually increased and reached above the pre-operative level. A significant low level creatinine clearance rate was observed in on-pump group. Renal function was better preserved in patients undergoing off-pump in comparison to on-pump coronary artery bypass grafting.